2020
DOI: 10.1111/hel.12683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of twice a day, bismuth‐containing quadruple therapy using high‐dose tetracycline and metronidazole for second‐line Helicobacter pylori eradication

Abstract: Background/Aims Conventional second‐line, bismuth‐containing quadruple therapy is administered four times a day. We aimed to evaluate the efficacy and safety of twice a day administration compared to the four times a day therapy. Methods Medical records of consecutive patients with positive 13C‐urea breath tests (UBTs) after first‐line eradication were reviewed. From December 2018 to June 2019, 100 consecutive 13C‐UBT‐positive patients received tetracycline 1 g, metronidazole 750 mg, bismuth subcitrate 300 mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…Second-line eradication regimen (bismuth subcitrate 300 mg, metronidazole 750 mg, tetracycline 1 g, and pantoprazole 20 mg twice a day for 1 week) was provided to all 89 eradication failure patients based on our recent study. 17 Among 41 patients in the tegoprazan group and 48 patients in the lansoprazole group, 38 and 46 patients underwent 13 C-UBT after 5 weeks at our center, respectively. The remaining five patients wanted to undergo confirmation tests at other centers.…”
Section: Resultsmentioning
confidence: 98%
“…Second-line eradication regimen (bismuth subcitrate 300 mg, metronidazole 750 mg, tetracycline 1 g, and pantoprazole 20 mg twice a day for 1 week) was provided to all 89 eradication failure patients based on our recent study. 17 Among 41 patients in the tegoprazan group and 48 patients in the lansoprazole group, 38 and 46 patients underwent 13 C-UBT after 5 weeks at our center, respectively. The remaining five patients wanted to undergo confirmation tests at other centers.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, BQT is administered four times daily, which may also reduce patient compliance. To overcome this, twice daily BQT regimens have been introduced, and studies in South Korea have demonstrated their effectiveness [44,45]. Kim et al demonstrated that twice daily BQT for 1 week was as effective and safe as the conventional four times daily BQT (93.9% vs. 92.9%) [45].…”
Section: Bismuth Quadruple Therapymentioning
confidence: 99%
“…To overcome this, twice daily BQT regimens have been introduced, and studies in South Korea have demonstrated their effectiveness [44,45]. Kim et al demonstrated that twice daily BQT for 1 week was as effective and safe as the conventional four times daily BQT (93.9% vs. 92.9%) [45]. In addition, most patients show good compliance, and the eradication rate of the twice-daily BQT is high (88.2% (ITT) and 98.4% (PP)) [44].…”
Section: Bismuth Quadruple Therapymentioning
confidence: 99%
“…Bismuth remains a useful second‐line option and a study in Korea looking at 15 years of data for the drug in treatment failures suggests an overall eradication rate of 79% with no significant changes over the period in question (2003 to 2018) and adverse events in 57% of patients 77 . Another Korean study showed even better results with 93% of second‐line patients using bismuth‐based therapy with twice‐daily dosing being equally efficacious as four times daily dosing 78 . In China, a study on BQT used as a rescue therapy comparing amoxicillin plus berberine vs. tetracycline plus furazolidone found similar eradication rates (76% vs 77%) with a significantly lower rate of adverse events in the amoxicillin and berberine group 79 .…”
Section: Bismuth‐based Therapymentioning
confidence: 99%